Apakah Pendapatan Perempuan Dapat Mengurangi Kemiskinan? Bukti Data Panel di Indonesia - Gunawan Adnan; Khairul Amri (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This research aims to analyze the effect of women's income on poverty reduction. Using a panel dataset of 32 provinces in Indonesia with time series data for the period of 2010-2018, the analysis model used is the fixed-effect method of the panel regression and the Panel Granger causality test. The study points out that women's income has a significant effect on poverty reduction. The greater women's income, the lower the poverty rates. Panel Granger causality test indicates that there is a bidirectional between women's income and poverty rate. The poverty causes women's income, and women's income also causes poverty rates. Therefore, local governments in Indonesia should formulate regional development policies that oriented towards increasing women's involvement in productive economic activities. The policy is not only able to improve the welfare of women, but also contribute positively to reducing poverty rates